2018
DOI: 10.1021/acsnano.7b06758
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectrification-Induced Self-Assembly of Macro-Sized Polymer Beads on a Nanostructured Surface for Self-Powered Patterning

Abstract: Here we report an electrostatic-templated self-assembly (ETSA) method for arbitrarily patterning millimeter-sized polymer beads on a nanostructured surface without using an extra voltage source. A patterned electrode underneath an electrification layer generates "potential wells" of the corresponding pattern at predefined window sites, which capture and anchor the beads within the window sites by electrostatic force. Analytical calculation is combined with numerical modeling to derive the electrostatic force a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…By shaking this tube, electrostatic interactions directed the self-assembly of these particles on the patterned surfaces. Conversely, Wang et al agitated millimeter-sized nylon beads in a container and subsequently deposited these particles on a separately charged electrification layer on which the particles assemble precisely on sequentially ordered sites. Collectively, these and other studies highlight the ability of tribocharging to direct the self-assembly of particles.…”
Section: Introductionmentioning
confidence: 99%
“…By shaking this tube, electrostatic interactions directed the self-assembly of these particles on the patterned surfaces. Conversely, Wang et al agitated millimeter-sized nylon beads in a container and subsequently deposited these particles on a separately charged electrification layer on which the particles assemble precisely on sequentially ordered sites. Collectively, these and other studies highlight the ability of tribocharging to direct the self-assembly of particles.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported an electrostatic self‐assembly method that facilitates the desired patterning of plastic pellets on a designed plate . Figure a shows the designed structure of the device, where a Teflon film with nanowire arrays on the surface (Figure b) is used as the electrification layer.…”
Section: Electrostatic Manipulator Driven By Tengmentioning
confidence: 99%
“…e) The electrostatic force of the ball at different locations. a–e) Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Electrostatic Manipulator Driven By Tengmentioning
confidence: 99%
“…Although the resulting patterns are highly controlled and arranged, the reproducibility of these devices seems highly sumptuous. Therefore, novel, cost-effective, and time-saving patterning methods have been investigated lately. , One of the proposed methods by Murillo et al focuses on the ZnO preference medium, where the nucleation and growth of the nanostructures take place on a certain seed layer comparatively faster than on the other thin-film layer . The study reports that the growth of patterned ZnO nanosheet arrays on the growth promoter aluminum nitride (AlN) seed layer is 4 times faster than that on neighboring gold (Au) thin film.…”
Section: Introductionmentioning
confidence: 99%